Sistem Pengautomatan Jentera Pemungut Tandan Kelapa Sawit - Wan Ismail, Wan Ishak; Bardaie, Muhamad Zohadie; Othman, Zulkarnain (Universiti Putra Malaysia Press, 1997)
Shortage of labour, whether it exists throughout the year or occurs at the peak time of an operation, translates into higher production costs. The adoption of modern technologies and production process to increase productivity will free labour, which is very important for both the agriculture and manufacturing sectors. The aim of this project was to introduce agricultural robotics and automation in the agriculture sector. The objective was to automate a grabber machine for picking and collection of oil palm fruit bunches. The grabber was modified using a hydraulic power source and a light sensor control system. Solenoid operated control valve 4/3 and electrical relay were used as the hydraulic control system. Light sensor model E3JM-R4M4-G was used as a light control system. Generally, this project produced satisfactory results and capable of picking oil palm bunches in 55.4 seconds at an operated pressure of 50 bar. This operation will require less manpower, save time and will make the operation of harvesting oil palm fruit more interesting.